1996
DOI: 10.1021/jp952374y
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle X-ray Scattering and Mass Spectrometry Studies of γ-Irradiated C60 in Cyclohexane

Abstract: Intense (1.42 krad/min) γ-radiolysis of C 60 dissolved in cyclohexane (weak magenta-colored solution) to a total dose of 51 krad resulted in the formation of a new compound (muddy red in color) with a solubility of more than 30 times that of saturated C 60 in toluene. Low-power, laser desorption Fourier transform mass spectrometry (LD-FTMS) of the product yielded two ions at m/z ) 1539 and 1556, which correspond to [C 60 (cyclohexane) 10 -xH] + for x ) 23 and 6, respectively. Higher power laser desorption cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…Subsequent characterization of the product formed in γ-irradiated C 60 / cyclohexane solutions revealed that it is formed via radical addition to C 60 , but an analogous product was not found in the radiolysis of fullerene/CS 2 solutions. 15 Thus, it became clear that the hydrocarbon solvents play a key role in the radiolytic formation of low-mobility fullerene product ions. In order to elucidate this role, the mechanism of hydrocarbon radiolysis must be considered, critical elements of which are radicals, the ubiquitous reactants in most radiolysis mechanisms, 31 and the radical-sponge properties of C 60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent characterization of the product formed in γ-irradiated C 60 / cyclohexane solutions revealed that it is formed via radical addition to C 60 , but an analogous product was not found in the radiolysis of fullerene/CS 2 solutions. 15 Thus, it became clear that the hydrocarbon solvents play a key role in the radiolytic formation of low-mobility fullerene product ions. In order to elucidate this role, the mechanism of hydrocarbon radiolysis must be considered, critical elements of which are radicals, the ubiquitous reactants in most radiolysis mechanisms, 31 and the radical-sponge properties of C 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that preirradiation of fullerene/hydrocarbon solutions by 60 Co γ-radiation changes the radius of the tracer fullerene ions prompted a study to identify the radiolytic product by smallangle X-ray scattering (SAXS) and mass spectral analysis that was recently reported. 15…”
Section: Introductionmentioning
confidence: 99%
“…These scattering techniques measure scattered intensity as a function of momentum transfer, q , where q = 4π (sin θ)/λ (2θ is the scattering angle). They have already been applied to fullerene studies on a number of occasions. They provide useful structural probes in general, including the ability to measure the second virial coefficient ( A 2 ) in solution which has not been reported on explicitly thus far in the fullerene literature. The coherent scattered intensity for weakly or non-interacting systems is where n is the scattering particle number density [cm -3 ], Δρ = (ρ p − ρ s ) is the scattering length density difference between the particle and the solvent for SANS (or proportional to the electron density difference between the particle and solvent for SAXS) [cm -2 ], V is the solvent-excluded volume occupied by the particle [cm 3 ], and P ( q ) is the normalized form factor ( P (0) = 1) that describes the scattering profile as a function of angle or q .…”
Section: Introductionmentioning
confidence: 99%
“…Modeling studies had predicted the stability of C 60 dimers having a dumbbell shape, and the synthesis of such dimers has been achieved through other routes . Further analysis of the radiolytic product by mass spectral and small-angle X-ray scattering (SAXS), however, indicated that the γ-irradiated products of C 60 in cyclohexane are cyclohexyl adducts of C 60 , primarily C 60 (C 6 H 12 ) 10 . The SAXS data also indicated that some of the C 60 (C 6 H 12 ) 10 entities aggregate into dimers in toluene solution, and a more rigorous study of the ion mobilities in γ-irradiated fullerene solutions in several solvents did not definitively identify the product(s) .…”
Section: Introductionmentioning
confidence: 99%